Spectroscopic Pulsational Frequency and Mode Determination of the γ Doradus Star HD 189631. (2014) - Davie, M. W.; Pollard, K. R.; Cottrell, P. L.; Brunsden, E.; Wright, D. J.; De Cat, P.
Abstract: We present improvement and confirmation of identified frequencies and pulsation modes for the γ Doradus star HD 189631. This work improves upon previous studies by incorporating a significant number of additional spectra and precise determination of frequencies. Four frequencies were identified for this star: 1.6774 ± 0.0002 d −1, 1.4174 ± 0.0002 d −1, 0.0714 ± 0.0002 d −1, and 1.8228 ± 0.0002 d −1 which were identified with the modes ( l, m ) = (1, +1), (1, +1), (2, −2), and (1, +1) respectively. These findings are in agreement with the most recent literature. The prevalence of ( l, m ) = (1, +1) modes in γ Doradus stars is starting to become apparent and we discuss this result.